Response of Use of NPK Fertilizer and Concentration of Young Coconut Water on Growth and Yield of Long Bean (Vigna sinensis L.) - Robert A. Sole; Henny A. Raga; Uly J. Riwukaho; Abdonia W. Finmeta; Astrid Aryani Ndun; Joritha Naisanu; Darmanto F. Kisse (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Long bean (Vigna sinensis L.) is a vegetable commodity containing 2.70 mg protein, 2.30 mg fat, 44 cal calories, 7.80 mg carbohydrates, 347 mg phosphorus, 47 mg calcium, 335 SI vitamin A, 0.39 mg B vitamins. , 21 mg of vitamin C and 88.50 mg of water. Production of Vigna sinensis L in NTT in 2019-2021 continues to increase but the phenomenon of rising long bean prices indicates that long bean production needs to be increased. One of the efforts made is to increase the availability of soil nutrients through fertilization. The aim of the study was to determine the interaction effect of NPK dosage and young coconut water concentration on the yield of long bean plants. The research was conducted in June-July 2022 using the Randomized Block Design (RBD) experimental method with 2 factors and 3 treatment levels, namely: Factor I = NPK Fertilizer (A) and Factor II = Concentration of young coconut water (K). The results obtained: The treatment of NPK fertilizer and young coconut water had a very significant effect on the growth components of long bean plants as indicated by differences in plant height, number of leaves, number of pods and pod weight. The interaction between the application of NPK fertilizer (NPK 250 kg/ha) and the concentration of young coconut water (90% /1L) gave the best results giving the best results on the average plant height, number of leaves, number of pods and pod weight of long bean plants.